A STOCK ADDRESSING: An Essential Tool for Inventory Accuracy - Miranda, Natalia Aparecida (Revista Interface Tecnológica, 2024)
Stock addressing is an essential practice for ensuring inventory accuracy in a company. It consists of assigning specific locations to each stock item, making it easier to locate products quickly and accurately. Inventory management is a crucial process aimed at optimizing the use of corporate resources and maximizing positive results (Rufino, 2009). Efficient stock management not only helps to reduce costs, but also to improve operational efficiency and customer satisfaction. When it comes to a company’s stock, competent management can lead to greater profitability in distribution services to customers and consumers. This is achieved through effective planning and control of handling and storage activities, the main aim of which is to facilitate the flow of products (Ballou, 2007). According to Viana (2002), precision in the location, organization and identification of products has a direct impact on inventory costs. When an item is not found, this can result in delays in orders and, in some cases, even the need to produce the product again. This situation entails additional costs for the company and compromises reliability in the eyes of consumers. This article reviews the main inventory management strategies with the aim of optimizing companies’ operational efficiency. Efficient storage is essential for the best use of space, efficient use of manpower, easy access to products, maximum protection for items and good quality storage and efficient handling. Inventory management, as a branch of business administration, involves planning and controlling stocks of materials or products. Well-planned strategies can reduce costs and ensure the proper performance of various business processes and functions.